2001
DOI: 10.2466/pr0.2001.89.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Anxiety among Eighth-Grade Students of the United Arab Emirates

Abstract: To investigate the mathematics anxiety of 159 students in Grade 8 (M age = 14.3 yr.) in the United Arab Emirates a 28-item anxiety scale was administered. Analysis indicated some mathematics anxiety. Also, boys and girls scored significantly differently as boys had the higher mean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…However, there are also many studies that show no gender differences in MA [3,5,7,10,29,52-61]. There are indeed a few studies that have found higher MA levels in males than in females [62-64]. …”
Section: Introductionmentioning
confidence: 99%
“…However, there are also many studies that show no gender differences in MA [3,5,7,10,29,52-61]. There are indeed a few studies that have found higher MA levels in males than in females [62-64]. …”
Section: Introductionmentioning
confidence: 99%
“…It is essential to understand the significance of instructional technology in helping eighth grade students perform well in mathematics in the TIMISS. Also, Abed [34] spots the significance of understanding students' level of math anxiety in the UAE students. Technology may help in reducing such math anxiety, with flexible and multiple learning tools.…”
Section: General School Resourcesmentioning
confidence: 99%
“…Instead, Devine et al [30] reported math anxiety to be a significant predictor of performance in females but not males, whereas Miller and Bichsel [31] found that math anxiety was more predictive of basic math performance in males than in females. Concerning the magnitude of the anxiety experienced by students, the findings are also mixed, including greater levels of math anxiety in females than in males [32,33], in males than in females [34], or no gender differences [35]. Interestingly, Hembree [22] reported that although math anxiety was higher in female students, it did not predict their math performance.…”
Section: The Selected Dispositionsmentioning
confidence: 99%